Abordagem temática na educação em ciências: um olhar à luz da epistemologia fleckiana - Magoga, Thiago Flores (2017)
The present master’s research held as base the discussion of actions paved by the curricular perspective of Thematic Approach (TA), through elements of the epistemology of Ludwik Fleck. Based on the fundaments of Freirean ideals, the proposal of thematic approach has been labeled by the field’s literature as an alternative for overcoming the problems regarding school’s curricular context. Despite such label, it was noted the inexistence of papers that approach which are the subjects who, within the field, build and disseminate knowledge regarding the curricular approach. Utilizing this realization as a prerogative, the following research problem is proposed: How is constituted the exoteric circle of researchers which, in the field of Science Education, develops actions by the Thematic Approach? Which theoretical and practical elements aid in the characterization of the Style of Thought of this collective?. With the goal to answer this questions, initially, a research for papers was made in some of the main journals of the field, such as: “Ciência & Educação”, “Ensaio: Pesquisa em Educação em Ciências”, “Investigações em Ensino de Ciências” e “Revista Brasileira de Pesquisa em Educação em Ciências”.Based on the thirteen articles selected during the bibliographical review, it was possible to make other questionings regarding how the thematic approach has been thought and worked within the field, in addition to identify the names of the main personalities who promote actions and build knowledge relative to this perspective. Past this identification, a second phase of the research was executed, constituted by interviews with five of the six main specialists who constitute the exoteric circle regarding the Thematic Approach. Afterward the analysis of the interviews, it was possible to discuss characteristics regarding these subjects, and therefore initiate the process of characterization of the style of thought of this collective. Supported by the interviews and selected works, along the first phase of the research, aided by the Discursive Textual Analysis as a method for analysis, it was possible to identify four categories: i) The development of papers: contexts and conceptions; ii) Freirean presuppositions as base (divides in other three categories); iii) Elements regarding the perspective of TA (divided in other four categories); iv) Challenges: how to overcome them?. The description and characteristics of the categories enable to characterize the style of thought of the exoteric circle, which is strongly marked by a Freirean bias and structured based on actions through formative processes and in a group context. It was also noticed that the identified exoteric circle organize its discussions and practices based on real demands which, having them as base, knowledge on the perspective of question and transform that reality can be constructed.